(untitled) (KULT_online, 2015)
The conference volume Präsenz und Evidenz fremder Dinge im Europa des 18. Jahrhunderts (Presence and Evidence of Unfamiliar Things in 18th-century Europe), edited by Birgit Neumann, aims to identify and understand the multitude of cultural, social, and political processes by which objects of exotic provenance were systematically appropriated, translated, and presented within an ‘enlightened’ European society. Based on a broad variety of objects, the volume’s contributions examine the extent to which the increased circulation and enhanced availability of exotic goods within a growing global market challenges Europe’s existing systems of classification and empirical cognition.